Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ijerph19052939
|View full text |Cite
|
Sign up to set email alerts
|

“No One Manages It; We Just Sign Them Up and Do It”: A Whole System Analysis of Access to Healthcare in One Remote Australian Community

Abstract: Objective: To assess the accessibility, availability and utilisation of a comprehensive range of community-based healthcare services for Aboriginal people and describe contributing factors to providing effective healthcare services from the provider perspective. Setting: A remote community in New South Wales, Australia. Participants: Aboriginal and non-Aboriginal health and education professionals performing various roles in healthcare provision in the community. Design: Case study. Methodology: The study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…However, Kuruvilla et al 's (46) study, which analysed case studies from widely differing social, economic, geographic, cultural and historical contexts, noted that despite the heterogeneity of their case studies, there were strong similarities identified in how different sectors collaborated. (53) identified through their analysis was the under-servicing and over-servicing among a variety of Aboriginal healthcare services in the community, which provided insight into the 'systemic barriers to interagency cooperation' (53). These findings were attributed to poor resourcing and incentivisation for health providers to coordinate their services (53).…”
Section: Intersectoral Collaborationmentioning
confidence: 99%
See 3 more Smart Citations
“…However, Kuruvilla et al 's (46) study, which analysed case studies from widely differing social, economic, geographic, cultural and historical contexts, noted that despite the heterogeneity of their case studies, there were strong similarities identified in how different sectors collaborated. (53) identified through their analysis was the under-servicing and over-servicing among a variety of Aboriginal healthcare services in the community, which provided insight into the 'systemic barriers to interagency cooperation' (53). These findings were attributed to poor resourcing and incentivisation for health providers to coordinate their services (53).…”
Section: Intersectoral Collaborationmentioning
confidence: 99%
“…While there is research that addresses intersectoral collaboration in Aboriginal primary healthcare settings, studies tend to advocate for the importance of intersectoral collaboration within broader research scopes and do not directly address or interrogate how collaboration plays out ( 47–52 ). A recent study conducted by Osborn et al ( 53 ) in a remote New South Wales community researched a variety of community-based healthcare services for Aboriginal people, including local ACCHOs. A key theme Osborn et al ( 53 ) identified through their analysis was the under-servicing and over-servicing among a variety of Aboriginal healthcare services in the community, which provided insight into the ‘systemic barriers to interagency cooperation’ ( 53 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals have made many efforts to explore healthcare services for the aged. Some designs may play an important role in senior citizens' healthcare [16,17]. However, there exist some studies that are not very successful in large-scale application.…”
Section: Introductionmentioning
confidence: 99%